1997
DOI: 10.1126/science.278.5343.1641
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Additive Effects of Central POMC and Leptin Pathways on Murine Obesity

Abstract: The lethal yellow (AY/a) mouse has a defect in proopiomelanocortin (POMC) signaling in the brain that leads to obesity, and is resistant to the anorexigenic effects of the hormone leptin. It has been proposed that the weight-reducing effects of leptin are thus transmitted primarily by way of POMC neurons. However, the central effects of defective POMC signaling, and the absence of leptin, on weight gain in double-mutant lethal yellow (AY/a) leptin-deficient (lepob/lepob) mice were shown to be independent and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
126
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(143 citation statements)
references
References 22 publications
(2 reference statements)
13
126
0
3
Order By: Relevance
“…Interestingly, if these mice are also made leptin de®cient by introducing the ob gene, they become even more obese, but are then sensitive to leptin. 23 This is easily explained as the leptin system is now operating from a zero baseline.…”
Section: Insights From Rodentsmentioning
confidence: 99%
“…Interestingly, if these mice are also made leptin de®cient by introducing the ob gene, they become even more obese, but are then sensitive to leptin. 23 This is easily explained as the leptin system is now operating from a zero baseline.…”
Section: Insights From Rodentsmentioning
confidence: 99%
“…By using a double mutant combining [Lep.sup.ob/ob] with the gene knockout [Npy.sup.-/-], it was shown that there are parallel pathways for leptin-related appetite control in the hypothalamus (Erickson et al 1996). (Boston et al 1997). Not all obesity is mediated by the leptin loop (Schonfeld-Warden & Warden 1997), not all leptin effects are mediated by appetite changes (Yu et al 1997), and diabetic symptoms are not joined inexorably with obesity (Hotamisligil et al 1996).…”
Section: Genetic Dissectionmentioning
confidence: 99%
“…Indeed, it is now clear that leptin-independent melanocortinergic CNS pathways exist. [103][104][105] Nonetheless, it is clearly established that a-MSH acting through MC4-Rs is a fundamental regulator of coordinated energy homeostasis. Key questions that remain include what metabolic and neural cues, beside leptin, drive the melanocortinergic neural circuits.…”
mentioning
confidence: 99%
“…As noted, leptin-independent melanocortinergic pathways also exist. [103][104][105] Therefore, our laboratory has recently tested the extent to which Arc POMC neurons contribute to CNS leptin signaling by using the Cre/loxP system. 103 First, transgenic mice expressing Cre in POMC neurons (POMC-Cre mice) were generated by using a POMC bacterial artificial chromosome.…”
mentioning
confidence: 99%